2019
DOI: 10.1007/s00445-019-1331-8
|View full text |Cite
|
Sign up to set email alerts
|

The crater lake of Ilamatepec (Santa Ana) volcano, El Salvador: insights into lake gas composition and implications for monitoring

Abstract: Here are the proofs of your article.• You can submit your corrections online or by fax.• For online submission please insert your corrections in the online correction form.Always indicate the line number to which the correction refers. • Please return your proof together with the permission to publish confirmation.• For fax submission, please ensure that your corrections are clearly legible. Use a fine black pen and write the correction in the margin, not too close to the edge of the page.• Remember to note th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 44 publications
1
6
1
Order By: Relevance
“…In this study, the calculated CO 2 /SO 2 population is scattered at low concentrations (<15 ppmv SO 2 ), along with observations at other volcanoes (e.g., Etna, Masaya, Pacaya) and they converge at more concentrated plume conditions (>15 ppmv SO 2 ) with values in the range of 2.1-3.3 (2.9 ± 0.6), behaving within the CAVA (2.0 ± 1.1) and the global arc gas signature (~2.5) . Hasselle et al (2019) already reported this behavior from measurements taken at Santa Ana, suggesting the scattering of the ratios due to the diluted nature of the plume and/or because of contributions from multiple gas sources (e.g., weakly degassing hydrothermal fumaroles and soil diffuse degassing on the inner crater slope). However, changes in the wind speed and direction should also be considered since some of the measurements were performed in a time span between 2 and 4 h, bringing different gas concentrations to the sampling point.…”
Section: So 2 Emission Fluxesmentioning
confidence: 77%
See 2 more Smart Citations
“…In this study, the calculated CO 2 /SO 2 population is scattered at low concentrations (<15 ppmv SO 2 ), along with observations at other volcanoes (e.g., Etna, Masaya, Pacaya) and they converge at more concentrated plume conditions (>15 ppmv SO 2 ) with values in the range of 2.1-3.3 (2.9 ± 0.6), behaving within the CAVA (2.0 ± 1.1) and the global arc gas signature (~2.5) . Hasselle et al (2019) already reported this behavior from measurements taken at Santa Ana, suggesting the scattering of the ratios due to the diluted nature of the plume and/or because of contributions from multiple gas sources (e.g., weakly degassing hydrothermal fumaroles and soil diffuse degassing on the inner crater slope). However, changes in the wind speed and direction should also be considered since some of the measurements were performed in a time span between 2 and 4 h, bringing different gas concentrations to the sampling point.…”
Section: So 2 Emission Fluxesmentioning
confidence: 77%
“…Furthermore, we see a medium to rich amount of water in the plume, when measurements were made under concentrated plume conditions (>15 ppm SO 2 ). Previous studies have reported variations in gas composition due to a combination of both scrubbing and meteorological conditions such as precipitation (e.g., Colvin et al, 2013;Hasselle et al, 2019). Field campaigns in this study were conducted during the dry season with sunny or cloudy days and no rain, so the above-mentioned effect did not influence our data.…”
Section: Plume Gas Compositionmentioning
confidence: 93%
See 1 more Smart Citation
“…For many Frontiers in Earth Science frontiersin.org years thereafter, very few studies have published SO 2 fluxes and water composition data (Colvin et al, 2013;Hasselle et al, 2019;Arellano et al, 2021). In a study presented by Hasselle et al (2019), SO 2 fluxes (Table 2) and measurements of gas composition (H 2 O, CO 2 , SO 2 , H 2 S and H 2 ) from gas plumes released from the crater lake were determined using the observatory's NOVAC station and a multicomponent gas analyzer system (MultiGAS), respectively. Total volatile fluxes of 20,200-30,200 ton/d and 900-10,167 t/d were reported for 2017 and 2018, respectively, which includes water vapor.…”
Section: Santa Anamentioning
confidence: 99%
“…PT was used only for measurements on Santa Ana's plateau (~200 m from the crater lake), during the 2019 survey. The SK instrument (Hasselle et al, 2019) is a smaller MultiGAS version designed for use onboard an unmanned aerial vehicle (UAV). In February 2019, measurements with SK were made over the crater lake at Santa Ana, with the UAV flying between several tens of meter above the lake and staying below the height of the crater rim and on the ground at the rim of San Miguel.…”
Section: Multigasmentioning
confidence: 99%